Joyce's Benefictions Perspectives in Criticism. - Bonheim, Helmut (Birmingham : University of California Press, 2021)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1964.
Intro -- Acknowledgments -- Contents -- 1. The Style of a Rebel -- 2. Bloom and Some Prototypes -- 3. Self and Society: The ""os"" Motif in Ulysses -- 4. The Father in Finnegans Wake -- 5. The Transformations of Mark -- 6. The King in Finnegans Wake -- 7. The Wake Pantheon -- 8. James Joyce's Epic of Anarchy -- 9. A Rebel's Métier: Comedy and Obscurity -- Notes
Description based upon print version of record.
JSTOR
Keywords: Joyce, James, -- 1882-1941.; Joyce, James, -- 1882-1941